Continued Fractions of Order Six and New Eisenstein Series Identities. (27th May 2014) - Adiga, Chandrashekar; Vanitha, A.; Surekha, M. S.
Abstract : We prove two identities for Ramanujan's cubic continued fraction and a continued fraction of Ramanujan, which are analogues of Ramanujan's identities for the Rogers-Ramanujan continued fraction. We further derive Eisenstein series identities associated with Ramanujan's cubic continued fraction and Ramanujan's continued fraction of order six.